A future university without humanities? - Ulrich Gumbrecht, Hans; Standford University (2016)
The specific function that the humanities could have of the university should be what I call riskful thinking. Now what do I mean by riskful thinking? I mean in the first case, very much inspired by Wilhelm von Humboldt, that riskful thinking is the thinking that produces questions instead of answers. Riskful thinking is a thinking that makes the world look more complicated and less solution-oriented. Riskful thinking is a thinking that produces alternative world views instead of catering to existing world views. Instead of reducing, riskful thinking tends to increase the complexity of the world by creating new problems.(Complete article in spanish language).